Improving Heart Failure Outcomes in Ambulatory and Community Care: A Scoping Study. (October 2017) - Jensen, Lorraine; Troster, Sarah M.; Cai, Kimberly; Shack, Avram; Chang, Ying-Ju Ruby; Wang, Dorothy; Kim, Ji Soo; Turial, Diva; Bierman, Arlene S.
Despite a large body of literature testing interventions to improve heart failure care, care is often suboptimal. This scoping study assesses organizational interventions to improve heart failure outcomes in ambulatory settings. Fifty-two studies and systematic reviews assessing multicomponent, self-management support, and eHealth interventions were included. Studies dating from the 1990s demonstrated that multicomponent interventions could reduce hospitalizations, readmissions, mortality, and costs and improve quality of life. Self-management support appeared more effective when included in multicomponent interventions. The independent contribution of eHealth interventions remains unclear. No studies addressed management of comorbidities, geriatric syndromes, frailty, or end of life care. Few studies addressed risk stratification or vulnerable populations. Limited reporting about intervention components, implementation methods, and fidelity presents challenges in adapting this literature to scale interventions. The use of standardized reporting guidelines and study designs that produce more contextual evidence would better enable application of this work in health system redesign.